1999
DOI: 10.1007/s12110-999-1011-z
|View full text |Cite
|
Sign up to set email alerts
|

Lineage interests and nonreproductive strategies

Abstract: The nonreproductive role of religious women in the European Middle Ages presents the ideal forum for the discussion of elite family strategies within a historical context. I apply the evolutionary concept of kin selection to this group of women in order to explain how a social formation in which religious women failed to reproduce benefited medieval noble lineages. After a brief review of the roles of noble women in the later Middle Ages, I identify two benefits that nonreproductive women provided within a pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Similar points are made by Boone [40] in his study of the fifteenth century Portugese nobility, and by Hill [51] in her evolutionary analysis of the situation of medieval religious women. Summers' paper on the evolutionary ecology of despotism [52] makes an argument on similar lines in many respects to that presented here, noting that aristocratic endogamy was a further means of ensuring the continuing existence of lineage land holdings (cf.…”
Section: Wealth and Reproductive Successsupporting
confidence: 67%
“…Similar points are made by Boone [40] in his study of the fifteenth century Portugese nobility, and by Hill [51] in her evolutionary analysis of the situation of medieval religious women. Summers' paper on the evolutionary ecology of despotism [52] makes an argument on similar lines in many respects to that presented here, noting that aristocratic endogamy was a further means of ensuring the continuing existence of lineage land holdings (cf.…”
Section: Wealth and Reproductive Successsupporting
confidence: 67%
“…Our results help clarify what conditions are necessary for celibacy to appear and be maintained through kin-selected benefits. Genealogical analyses of Medieval and Early Modern European nobility have shown that more children were directed to religious careers in higher social strata [22] and a comparison of two French noble families has suggested that lineages with more celibates were more likely to persist [23]. Both our model and data have shown that celibacy can appear and be maintained in a society without social stratification and hypergamy, two factors that have previously been suggested to be crucial [22,23,50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Genealogical analyses of Medieval and Early Modern European nobility have shown that more children were directed to religious careers in higher social strata [22] and a comparison of two French noble families has suggested that lineages with more celibates were more likely to persist [23]. Both our model and data have shown that celibacy can appear and be maintained in a society without social stratification and hypergamy, two factors that have previously been suggested to be crucial [22,23,50,51]. It has been argued that psychological reinforcement mechanisms and costly ostracism in the case of abandonment of the monastery are key for religious celibacy to appear and be maintained, and they might be used as proximate mechanisms for parents and religious institutions to enforce their own interests [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations